Corn and soybean response to sulfur fertilizer in West Tennessee. Issue 1 (4th April 2021) - Cannon, Kacey; McClure, M. Angela; Yin, Xinhua; Sams, Carl
Abstract: With improved crop yields and reduced atmospheric S deposition, Mid‐South U.S. soils may require S fertilization in deficient soils. The objectives of this study were to identify optimal at‐planting S rate for corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] yield, and evaluate the impact of S rate on crop growth, leaf nutrient level, and seed S. Small plot replicated field studies were conducted in 2015 and 2016 at a S‐deficient site in Milan, TN. Ammonium sulfate [(NH4 )2 SO4 ] was broadcast applied at planting at 0, 10, 20, and 30 lb S acre –1 . Soybean leaf S concentration at early bloom was similar to the zero S control, but concentrations of Fe, Mn, and Cu were reduced, and Zn was increased. These effects increased with S rate. Corn leaf tissue S concentration increased with S rate at sixth‐leaf and silking, while Fe, Mn, and Cu decreased as S rate increased, similar to the soybean experiment. Soybean seed S level increased with rate of S, while corn seed S increased with lowest S rate but did not respond to S rate. Seed N and seed weight were not affected by S rate for either crop. The small increase in soybean yield was not significant. Corn yield increased with applied S in both years. Overall, application of S fertilizer at ≥10 lb S acre –1 improved corn but not soybean yield in a low soil organic matter (SOM), S deficient medium‐textured soil. Core Ideas: Sulfur fertilizer increased grain yield in corn but not soybean. Corn leaf S and soybean seed S increased with S rate. Sulfur did not affect seed weight or seed N in corn or soybean.